The effect of giving shallot compress (Allium Ascalonicum l.) on breast swelling in postpartum mothers: A pre-experimental study - Zelharsandy, Vika Tri; Soleha, Marchatus; Sepiwiryanti, Wika (School of Health Sciences Al-Ma'arif, 2026)
Background: Breast swelling or breast engorgement is a common problem experienced by postpartum mothers and often causes pain, discomfort, and difficulties in breastfeeding. Non-pharmacological and culturally acceptable interventions are needed to manage this condition safely and effectively. Shallot compress (Allium ascalonicum L.) has been traditionally used to reduce inflammation and swelling, but scientific evidence supporting its effectiveness in postpartum breast swelling remains limited. Objective: This study aimed to examine the effect of giving shallot compress (Allium ascalonicum L.) on breast swelling in postpartum mothers. Methods: This study employed a quasi-experimental design with a one-group pretest–posttest approach. The sample consisted of 20 postpartum mothers experiencing breast swelling, selected using purposive sampling. The intervention involved the application of a shallot compress to the swollen breast area according to a standardized procedure. Breast swelling severity was assessed before and after the intervention using observation and checklist instruments. Data were analyzed using descriptive statistics and inferential analysis with a significance level of 95%. Results: The results showed a clear reduction in breast swelling severity after the intervention. Before the intervention, most participants experienced heavy breast swelling, whereas after the intervention no participants remained in the heavy category. The mean breast swelling score decreased from 2.50 before the intervention to 1.45 after the intervention, indicating a significant improvement in breast swelling conditions among postpartum mothers. Conclusion: The application of shallot compress (Allium ascalonicum L.) was effective in reducing breast swelling severity in postpartum mothers. This intervention provides a safe, low-cost, and non-pharmacological option to support breastfeeding comfort during the postpartum period.